2018
DOI: 10.1007/s40263-018-0553-1
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement in Cognitive Function as Measured by NeuroTrax in Patients with Relapsing Multiple Sclerosis Treated with Natalizumab: A 2-Year Retrospective Analysis

Abstract: Background Cognitive impairment affects many patients with multiple sclerosis (MS). NeuroTrax, a computerized cognitive screen that can be administered during routine clinical care, provides a consistent, validated, objective cognitive profile measure with a global cognitive score (GCS) and seven individual domain scores. Natalizumab is an efficacious therapy for relapsing MS, demonstrating reductions in disability worsening and MS disease activity measured by magnetic resonance imaging. Objective The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Testing time was approximately 45 min. The computerized cognitive battery has shown good test-retest reliability and construct validity relative to paper-based tests, including the frequently used Neuropsychological Screening Battery for MS, NSBMS, [3], as well as sensitivity to effects of DMD in MS [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing time was approximately 45 min. The computerized cognitive battery has shown good test-retest reliability and construct validity relative to paper-based tests, including the frequently used Neuropsychological Screening Battery for MS, NSBMS, [3], as well as sensitivity to effects of DMD in MS [7].…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive impairment was significant only at disease duration greater than five years suggesting the existence of an early therapeutic window [5]. However, the effects of disease modifying drugs (DMD) on cognitive impairments in MS have not been thoroughly studied [6], though several DMD have demonstrated a beneficial effect on cognitive performance [7] and spared brain atrophy [810], thus showing the potential to decrease cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Natalizumab administered intravenously every 4 weeks (Q4W 1 ) is an efficacious treatment for relapsing forms of multiple sclerosis (MS), as demonstrated by randomized clinical trials and real-world evidence (Butzkueven et al, 2020;Capra et al, 2020;Gudesblatt et al, 2018;Horakova et al, 2020;Perumal et al, 2019;Polman et al, 2006;Wiendl et al, 2020). However, Q4W natalizumab dosing is associated with a risk of progressive multifocal leukoencephalopathy (PML) in anti-JC virus (JCV) antibody-positive patients (Bloomgren et al, 2012;Ho et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that DMTs may improve cognitive function or slow cognitive decline, [136][137][138][139][140][141] although it is unclear if this is due to a reduction in MRI disease seen with these agents. The overall evidence does not link any specific agent consistently with improvement in cognitive function nor does it support switching agents to benefit cognition.…”
Section: Mrimentioning
confidence: 99%